2018
DOI: 10.14740/gr966w
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Hepatic Percutaneous Endoscopic Gastrostomy Tube Placement: A Case Report of A Rare Complication and Literature Review

Abstract: Percutaneous endoscopic gastrostomy (PEG) tubes have emerged as the standard of care for long-term enteral feeding. This procedure is relatively safe; however, complications do occur, and one of the most dreaded complications is trauma to the surrounding organs. Hepatic injury during PEG placement is an extremely rare complication of the PEG procedure, with a handful of cases described in the medical literature. We describe the case of an accidental trans-hepatic placement of a PEG tube in a 78-year-old morbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…73 Hepatic injury has also been reported rarely but can have potentially severe consequences resulting from a significant bleed. 74 Similar to the colon injury reports, these also can either present as acute severe bleeding episodes requiring operative intervention or IR to embolize active bleeding, or as pain or infection in a more delayed fashion. Chhaparia et al described six reported cases of transhepatic PEG placement, all of which had successful transillumination.…”
Section: Peg and Intrabdominal Organ Injurymentioning
confidence: 79%
See 1 more Smart Citation
“…73 Hepatic injury has also been reported rarely but can have potentially severe consequences resulting from a significant bleed. 74 Similar to the colon injury reports, these also can either present as acute severe bleeding episodes requiring operative intervention or IR to embolize active bleeding, or as pain or infection in a more delayed fashion. Chhaparia et al described six reported cases of transhepatic PEG placement, all of which had successful transillumination.…”
Section: Peg and Intrabdominal Organ Injurymentioning
confidence: 79%
“…Chhaparia et al described six reported cases of transhepatic PEG placement, all of which had successful transillumination. 74 Three of the patients did require a laparotomy but rest were managed conservatively with tube removal, especially when presented late. We do recommend reviewing any radiological data available prior to the procedure.…”
Section: Peg and Intrabdominal Organ Injurymentioning
confidence: 99%
“…tolerating tube feeds. 32,33 In symptomatic patients, it is prudent to stop tube feeds and to replace the tube once a mature tract has formed to prevent worse complications.…”
Section: Mild Adverse Eventmentioning
confidence: 99%
“…34,35 Ultrasound prior to the procedure to confirm position of the inferior liver edge is a potential way to avoid transhepatic placement of gastrostomy tubes. 32 Massive hepatosplenomegaly may be a relative contraindication to PRG if a safe window of access is not attainable.…”
Section: Mild Adverse Eventmentioning
confidence: 99%
“…Life-threatening or severe complications are rare and include gastric perforation, peritonitis, vascular or organ trauma, metastatic tumor spread, necrotizing fasciitis, and buried bumper syndrome [7]. Traversing the liver is an extremely rare but very serious complication of PEG tube placement with only 16 previous case reports in the literature [8][9][10][11][12][13][14][15][16][17][18][19][20]. We report a case of transhepatic insertion of a PEG tube in a 92-year-old female incidentally discovered on imaging and review the literature on this complication.…”
Section: Introductionmentioning
confidence: 99%